Estimating Consumer Integrated Pest Management (IPM) Knowledge - Andrew H. Jeffers; Bridget K. Behe; Michael Vassalos; William C. Bridges; Sarah A. White (HortTechnology)
Landscape pest management is challenging and has historically relied on traditional pesticide rotations. Integrated pest management (IPM) is a combination of chemical and nonchemical control methods to reduce pesticide usage and reliance. Scant literature is available on consumer knowledge of IPM. To address this gap in knowledge, 1000 respondents were surveyed to evaluate their understanding of IPM. Questions were vetted using the Delphi method with nine industry and academic experts. More than 75% of respondents had some knowledge or were very knowledgeable of IPM. More education contributed strongly to more knowledge of IPM. The results of this study are comparable to those of another study and show that consumers are more knowledgeable than horticultural professionals may realize. Horticultural professionals could capitalize on this potential new market, with the understanding that some consumers would still need guidance to understand the myriad components of an IPM program. Future studies should evaluate consumer willingness to pay for plant products grown using IPM techniques such as biological controls and reduced chemical–pesticide inputs and, specifically, whether consumers are willing to pay for such biological control products or landscape scouting services. Future studies should also examine an IPM certification of ornamental plants and how they might perform compared to traditionally grown plants or certified organic-grown plants.